The Discourse Network Analysis of Rempang Eco City Policy in the Digital News Media - Abdur Rahman Hakim; Herna; Reza Praditya Yudha (Ikatan Sarjana Komunikasi Indonesia, 2025)
This study examines how Indonesia’s mainstream digital media—Kompas, DetikNews, and CNN Indonesia—constructed policy discourse on the Rempang Eco City development between January 2023 and May 2025. Employing Discourse Network Analysis (DNA), the research maps relational patterns among actors, concepts, and positions extracted from news articles, providing a dual analytical lens: structural and interpretive. The findings reveal two dominant discourse coalitions: one promoting economic development and investment legitimacy, and the other emphasizing human rights, environmental risks, and Indigenous resistance. These coalitions reflect discursive polarization within public debates on national strategic projects. Conceptually, the study contributes to Communication Policy Theory by situating media discourse as a site of symbolic governance, where policy legitimacy is negotiated through competing narratives. Methodologically, it demonstrates the utility of DNA in capturing actor alignments, discursive clusters, and coalition dynamics in fragmented media environments. The study underscores the critical role of digital news platforms not only as information intermediaries but as active agents shaping public perception and policy coherence. This research highlights the need for more communication-centered approaches in analyzing policy controversies and offers a replicable framework for mapping discursive power in development conflicts.